Report of XXV congress of the international academy of pathology Brisbane convention and exhibition centre, Queensland, Australia - Omar, Effat
Introduction The International Academy of Pathology (lAP) annual meeting plays an important role in updating the standard pathological diagnoses, encouraging the study of obscure disease etiologies and promoting active debate on controversial disease entities. In addition, it provides a platform for dynamic exchange of academic information and mutual collaboration between countries necessary for the prevention of diseases, especially communicable disease outbreak (such as the recent SARS and Bird flu epidemics), and in the subjugation of malignant diseases. Member countries take turn to host the meeting. Last year's meeting was in Thailand, this year is Australia and next year it will be in Beijing. Malaysian pathologists enthusiastically take part in these meetings, either as delegates, presenting research findings or as invited lecturers.(see. enclosed Program book). Conclusion On the whole, it was a very fruitful congress, and the participation was very rewarding. The amount of knowledge gained was tremendous. Further, it is always inspiring to listen to and be in presence of authorities in a particular field. This inspiration is necessary for one to continue to aim for excellence. The paper presentation was a success, although no awards was won, since it led to formation of new links and open new door of opportunity for further studies and collaboration to be performed.